(untitled) (Sociologisk Forskning, 1993)
Family policies in the EC-countries from a female perspective The purpose of this article is to problematize the family policies in the EC-countries from a female perspective. The article emphasizes the family policies as motherhood policies in the twelve EC-countries. In my examples, I have focussed particularly on the phase of childbirth and the care for small children in the family cycle. My interest is to analyze the implication of the family policies for women’s life chances, integrity and autonomy. In the article, an overview of the rules that afflict mothers’ possibilities to be employed and attain autonomy is presented. A majority of the EC-countries have introduced separate taxation between spouses with the motivation to stimulate women’s employment. Many rights concerning possibilites to conciliate employment and family have been introduced in the EC-countries during the late 1980’s and the early 1990’s. The rule systems are difficult to grasp and appear to work in the opposite direction in their consequences, which renders comparisons between the countries more difficult. Many questions can be asked concerning the joint effects of the taxation system, allowance regulations and rights concerning possibilities to conciliate employment and family for women in different social strata respectively, and detailed studies of how the rule systems work for these women in different social strata are required. A general conclusion is that mothers are nowadays granted the right to employment and the right to keep it when they have children. Men have almost in all EC-countries received extended possibilities to take leave in connection to their becoming fathers. Simultaneously, married/cohabitant women’s economic dependence on men is asserted/reinforced by tax-systems, allowance regulations and shortages of child care. I also stress the need to study rules within the different social security systems in detail. This becomes particularly relevant when one studies women, since social security systems are based on paid work. Since women have salaried work on odder premises, they run the risk of not qualifying for support or not being insured at all. In the article, I argue the family policies shall be directed more particularly towards theproblems of the women and the children in the families. The gender-neutral perspective that in most cases is pre-dominant is in fact a male perspective. It is chiefly mothers who put the most effort and time into families. It is mothers that de facto have the main responsibility for the children in the family. Therefore it is also essential that the family policies more consciously proceed to strengthen the women’s (and the children’s) position and direct measures towards the problems that mothers have in families.